Uma avaliação das operações de crédito do Estado do Ceará no período de 2012-2023 - Machado, Monique Mayara Alves (2024)
The study investigates the impact of credit operations on public investments in a case study for the State of Ceará. Models estimated by Generalized Least Squares (GLM) for the level and growth rate of investments as a function of external, internal and global credit operations were applied following the Newey-West proposal, in a time horizon with data for the period between the first four months of 2012 and the last of 2023. The estimates allow us to infer that: i) the total volume of credit operations in relation to the RCL contracted in the previous year does not impact the volume of public investments in proportion to the current RCL; ii) when disaggregating the types of credit operations, it was observed that external credit operations in relation to the RCL contracted in the previous year had a negative impact on the current level of public investments in proportion to the RCL, while, iii) the same impact observed for internal credit operations is positive. This divergence of qualitative effect in the significant impact of external and internal credit operations suggests a different purpose for the resources raised through the respective sources. The delay in the release of resources from credit operations already contracted due to slow execution of programs, management inertia in the application of resources after release by creditor banks or even the possible payment of debt for external credit operations, are shown as determinants of the negative result.